2022
DOI: 10.1007/s12210-022-01084-7
|View full text |Cite
|
Sign up to set email alerts
|

Plants and water in a changing world: a physiological and ecological perspective

Abstract: The reduction of greenhouse gases (GHGs) emission by replacing fossil energy stocks with carbon–neutral fuels is a major topic of the political and scientific debate on environmental sustainability. Such shift in energy sources is expected to curtail the accumulation rate of atmospheric CO2, which is a strong infrared absorber and thus contributes to the global warming effect. Although such change would produce desirable outputs, the consequences of a drastic decrease in atmospheric CO2 (the substrate of photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…On the other hand, a quantile-based definition may also underestimate the frequency of occurrence of CDs and their adverse impacts on terrestrial carbon uptake in drylands. Although plants in drylands can maintain photosynthesis with limited water supply through their morphology and physiology [21][22][23] , ecosystem productivity is predominantly controlled by water availability 24,25 . Frequent and severe droughts directly reduce carbon uptake in drylands, and dryland ecosystems contribute a large proportion to the interannual variability of global terrestrial carbon sink 26,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a quantile-based definition may also underestimate the frequency of occurrence of CDs and their adverse impacts on terrestrial carbon uptake in drylands. Although plants in drylands can maintain photosynthesis with limited water supply through their morphology and physiology [21][22][23] , ecosystem productivity is predominantly controlled by water availability 24,25 . Frequent and severe droughts directly reduce carbon uptake in drylands, and dryland ecosystems contribute a large proportion to the interannual variability of global terrestrial carbon sink 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…npj Climate and Atmospheric Science (2024)23 Published in partnership with CECCR at King Abdulaziz University…”
mentioning
confidence: 99%
“…Li et al [30], Klein et al [31], and Naznin et al [32] also found that plants exposed to mixed R and B light exhibit high levels of Chlorophyll a (Chl a), Chlorophyll b (Chl b), total chlorophyll (Chl), and ETR, as well as the early development of non-photochemical quenching (NPQ), which enhances photosynthetic efficiency. Caferri et al [33] found that the photosynthetic rate and stomatal conductance of basil are higher under mixed light (R:B (75:25), R:G:B (60:20:20), and R:G:B (31:42:27)) than under monochromatic R light. Zhang et al [34] found that an R:B ratio of 7:3 increased the growth of Salvia miltiorrhiza Bunge as well as the content of rosmarinic acid and salvianolic acid B compared with monochromatic R and B light.…”
Section: Introductionmentioning
confidence: 99%